(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Reactive oxygen species are one of the major reasons for liver damage. The study investigates the hepatoprotective activity of Ethanolic Extract of Cissus Quadrangularis Linn of fruits against ethanol-induced hepatotoxicity. Fruit Powder of Cissus Quadrangularis was successively extracted with ethanol. Preliminary phytochemical tests were done. The hepatoprotective activity of the AST, ALT, ALP, ALB, BIT and BID were assessed in alcohol-induced hepatotoxicity rats. The EECQ showed the presence of alkaloids, carbohydrates, steroids, saponins and triterpenes, while alkaloids, carbohydrates and saponins were present Ethanol produced significant changes in physical (increased liver weight and volume), biochemical (increase in serum alanine transaminase, aspartate transaminase, alkaline phosphatase, direct bilirubin, total bilirubin, cholesterol, triglycerides and decrease in total protein and albumin level). Pre-treatment with EECQ extract significantly prevented the physical, biochemical, histological and functional changes induced by alcohol in the liver. The present study indicates that EECQ extract possessed potential hepatoprotective activity. This activity may be attributed due to the rich phytoconstituents of the plant extract.